Determination of drotaverine hydrochloride in dosage forms by its quenching effect on the luminescence of terbium complex - Alla Yegorova, Inna Leonenko, Daria Aleksandrova, Yuliya Scrypynets, Aleksandra Aleksandrova (Journal of Applied Pharmaceutical Science, 2013)
A new, simple, sensitive luminescence method for the determination of drotaverine hydrochloride is developed and validated. The Drotaverine hydrochloride can remarkably quench the luminescence intensity of the Tb3+ ion in terbium complex with 1-bythyl-4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxylic acid-(4-methyl-pyridin-2-yl)-amide (R) in aqueous solutions containing urotropine buffer (pH 7.5) at λex=317 nm and λem=545 nm. Under optimal conditions, the quenching of luminescence intensity is directly proportion to the concentration of Drotaverine hydrochloride in the range of 0.5-300 μg/mL and detection limit is 0.16μg/mL. This method was applied for the determination of Drotaverine hydrochloride in tablets “No-spa”.
Keywords: Drotaverine hydrochloride, luminescence intensity, q